2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319467
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight custom composite prosthetic components using an additive manufacturing-based molding technique

Abstract: Additive manufacturing techniques are becoming more prominent and cost-effective as 3D printing becomes higher quality and more inexpensive. The idea of 3D printed prosthetics components promises affordable, customizable devices, but these systems currently have major shortcomings in durability and function. In this paper, we propose a fabrication method for custom composite prostheses utilizing additive manufacturing, allowing for customizability, as well the durability of professional prosthetics. The manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The study showed the feasibility of its use by children in developing countries. Leddy et al [57] used additive manufactured molds to fabricate components for prosthetic hands with multiple and composite materials to achieve light weight and high stiffness. an AM system [11,43], uneconomic throughput and material cost [12,15], and limited material strength [41,46].…”
Section: Other Applicationsmentioning
confidence: 99%
“…The study showed the feasibility of its use by children in developing countries. Leddy et al [57] used additive manufactured molds to fabricate components for prosthetic hands with multiple and composite materials to achieve light weight and high stiffness. an AM system [11,43], uneconomic throughput and material cost [12,15], and limited material strength [41,46].…”
Section: Other Applicationsmentioning
confidence: 99%
“…Continuum mechanisms provide a passive compliance as the continuum structure reacts to any kind of disturbance with a deformation. The mechanism can therefore collide with the environment without being damaged, which is termed “mechanical robustness.” Mechanisms of this kind are used as finger joints in robotic 1 or prosthetic 2 hands, quadrupedal spines, 3 humanoid necks or spines, 4 or whole robotic arms made of serially attached mechanisms. 5 Furthermore, parallel continuum robots possess a similar design, with multiple continua in between two rigid platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The hope was to influence future prosthetic designs, to create lightweight hand prosthetics that are durable, customizable, and cost-effective. Finally, by using carbon fiber, they were able to build prosthetic hands that are half as heavy as regularly printed 3D hand, and one-quarter of the weight of a machined aluminum hand with more flexible joints [36].…”
Section: Additive Manufacturing Used For Prosthetic Devicesmentioning
confidence: 99%